(3QSGdI aj GdOZOZIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bhd Mfjf Hf ESMGb ai GdSHH GdPi EPG CeQQJ GdjO Ydi ehGVY ef GdHOf YQV ai Pdc GdehVY OZOZI Jchf eYgG VMc s
(3BNQgG (B:s
(3hdPdc deG cGf gPG GdehVY ef GdbOe cKjQ GdMS hcGf eY Pdc djfkG cGf jYQV dg GdOZOZI EPG CeQJ GdjO Ydjg EfbVi Gdbhd ai GdOZOZI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSI YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs